Boundary Control and Stabilization of an Axially Moving Viscoelastic String under a Boundary Disturbance - Kelleche, Abdelkarim (Mathematical Modelling and Analysis, 2017)
In this paper, we consider a system modelling an axially moving viscoelastic string subject to an unknown boundary disturbance. It is controlled by a hydraulic touch-roll actuator at the right boundary which is capable of suppressing the transverse vibrations that occur during the movement of the string. The multiplier method is employed to design a robust boundary control law to ensure the reduction of the transvesre vibrations of the string.